Academic Gratitude and the Purpose among Muslim Students: An Empirical Study - Nurul Wardhani (Journal of Social Research, 2025)
Academic gratitude plays an important role in shaping students’ psychological well-being and motivation; however, research on its association with purpose in life remains limited, particularly among Muslim students in Indonesia. On the other hand, many Muslim students experience confusion in determining life direction and the meaning of academic activities, which leads to stress, anxiety, and even depressive symptoms. Cultural pressures, discrimination, and lack of social support further exacerbate this condition, making the absence of a clear life purpose a significant issue affecting their well-being. This study aims to examine the relationship between academic gratitude and purpose in life among Muslim students. The participants consisted of 308 Muslim students in West Java recruited through convenience sampling. The instruments used were self-report questionnaires, namely the Gratitude Questionnaire-6 (GQ-6) to measure academic gratitude and the Claremont Purpose Scale (CPS) to measure purpose in life. Spearman correlation analysis revealed a moderately strong and significant positive relationship between academic gratitude and the purpose (r = 0.434; p < 0.01). These findings suggest that the higher the students’ academic gratitude, the clearer their sense of life purpose. Further research is needed to explore the influence of academic gratitude on purpose in life in different cultural and religious contexts to broaden the generalizability of the findings.